Optimizing healthy snacks for diabetics: Study of fiber and starch digestibility of glucomannan-modified Growol cookies - Desty Ervira Puspaningtyas; Puspita Mardika Sari; Silvia Dewi Styaningrum; Adi Sucipto; Dwita Mukti Rahmawati; Getha Puji Lestari (AcTion: Aceh Nutrition Journal, 2024)
Diabetes mellitus (DM) is an emergency health problem in the 21st century. High dietary fiber and resistant starch foods with low starch digestibility are solutions for DM. The addition of glucomannan to food can optimize the levels of dietary fiber, resistant starch, and starch digestibility. This study aimed to examine the optimization of dietary fiber, resistant starch, and starch digestibility in Growol cookies supplemented with glucomannan. Laboratory observations were conducted at the Universitas Respati Yogyakarta and Chemmix Pratama Yogyakarta Laboratory between July and September 2023. Cookies consisted of cookies A (negative control), B (positive control), C (modified 10-gram inulin), D (modified glucomannan 3%), and E (modified glucomannan 7%). Dietary fiber and resistant starch analyses were performed using the multi-enzyme method. Starch digestibility was determined by comparing the starch content obtained using the enzymatic method with that obtained using the acid hydrolysis method. Statistical analyses were performed using ANOVA and Kruskal-Wallis tests. There were differences in dietary fiber and resistant starch among the variants (p<0,001) with the highest being cookies E. There was no difference in starch digestibility between the variants (p=0,104) with the lowest being cookies E. In conclusion, glucomannan addition can optimize dietary fiber and resistant starch levels, as well as the starch digestibility of Growol cookies as a healthy snack for diabetics.